In Vitro and In Vivo Effects of Seaweed Extract on Carbohydrate Digestion and Availability. Issue 1 (2019) - Sveinsdottir, K.; Ingadottir, B.; Elidottir, A.S.; Geirsdottir, O.G.; PV, P.V. Jonsson; Ramel, A.
No abstract available